Pengaruh Konformitas dan Kepercayaan Diri Terhadap Kesehatan Mental Siswa di SMAN 6 Kab. Seluma, Provinsi Bengkulu - Andayani, Retno; Helpiyana, Helpiyana; Pratama, Candra (DAWUH : Islamic Communication Journal, 2022)
This research aims to see the influence that conformity and self-confidence have on the mental health of teenagers at SMAN 6 Seluma. The results of this research show that conformity and self-confidence have a very significant role in teenagers at SMAN 6 Seluma. Which can determine and have an impact on mental health. This research uses quantitative methods, the data collection technique is by distributing a questionnaire with 30 items distributed. The sample studied was teenagers at SMAN 6 Seluma. Data collection totaled 109 respondents. This research was analyzed using quantitative analysis using SPSS 20 by testing correlation regression, normality test, reliability test and R square. Based on the results of this research, it shows that the influence of conformity and self-confidence on the mental health of teenagers at SMAN 6 is always in the weak category, namely 45.5%.